Information Technology Service Management: Development over the Last 25 Years, Challenges, and Future Opportunities - Pattanayak, Santosh Kumar (Digital Repository of Theses, 2024)
Over the years, Information Technology (IT) has been able to establish itself as a vital tool for businesses to thrive in the modern world. Most of the business services are either a fully digital service or enabled by IT services. Over dependence on IT services demands IT service providers to provide a stable service that is in pace with the ever-changing demands of industry. Information technology service management (ITSM) has gained its popularity as it ensures that IT systems deliver a stable and evolving service as dictated by the business environment. Researchers have started taking interest on this field of IT, however, there is not much scholarly paper available for overall ITSM developments. This research project studied the journey of ITSM over the last 25 years, evaluate different frameworks available in the market and present the differences between various frameworks. It also evaluated the frameworks for implementation in various organizations. Further, this study examined future trends (such as Artificial Intelligence (AL)/ Machine Learning (ML) and challenges of ITSM implementation. As AI/ML is catching up very fast, this paper recommends future researchers to develop more and more models using AI/ML for improvements in IT services field.